Manipulating of polyacrylonitrile membrane porosity via SiO2 and TiO2 nanoparticles: Thermodynamic and experimental point of view. (30th November 2020) - Hamta, Afshin; Zokaee Ashtiani, Farzin; Karimi, Mohammad; Safikhani, Amir
Abstract : In this work, the membrane formation of the polyacrylonitrile (PAN) was investigated in the presence of different solvents named N ‐methyl‐2‐pyrrolidone (NMP) and dimethylformamide (DMF). In this way, two ternary systems water/NMP/PAN and water/DMF/PAN were studied and compared both experimentally and thermodynamically. According to the binodal data, changing the solvent from NMP to DMF could expand the two‐phase region, which was proved by Hansen solubility parameters. The binodal data were predicted and the results showed that the Flory‐Huggins results are in good agreement with experimental data with less than 2% deviation, which is important to have a rational design of porous membrane and appropriate prediction of its morphology. Furthermore, the effects of TiO2 and SiO2 nanoparticles were investigated on dope solution viscosity, thickness, porosity and contact angle of the membranes in both solvents. The results showed that the pattern of changes in characteristics was similar using each nanoparticle. Lower concentrations of nanoparticles enhance the porosity of the membranes and above the optimum amount, adding the NPs leads to decrement the porosity of the nanocomposite membranes. Finally, the fluxes of the manufactured membranes in both cases were examined using distilled water or oil‐in‐water emulsion as feed. The initial permeate flux of oil‐in‐water emulsion was increased from 62 to 73 L m −2 hr −1 using the membrane fabricated by DMF instead of NMP and this fact showed that the PAN membranes potentially can be used for oil/water separation due to the low fouling and hence, the low flux drop during the time.